Potential Role of Door Handles in the Spread of Drug Resistant Bacteria in Makerere University. - Immaculate Nabawanuka (Student's Journal of Health Research, 2021)
Background: The transmission of diseases caused by pathogenic bacteria is still a threat. One of the potential sources of bacterial diseases is the door handles. This study aimed at isolating, identifying bacteria, determining total bacterial load, and determining antibiotic susceptibility patterns of bacteria obtained from door handles in Makerere university. Methodology:  A total of 60 samples randomly scattered within the university were swabbed and analyzed for bacterial growth. Samples were inoculated on MacConkey and blood agar and then incubated at 37 ºC for 24 hours. All sample isolates were sub cultured and identified based on macro and micromorphology, and standard biochemical tests. The establishment of the total bacterial load was done using the standard plate count method. Antibiotic susceptibility testing was done using the disc diffusion method on Muller Hilton agar. Results: The following bacterial species and genera were obtained from door handles, staphylococcus aureus (30.8%), Coagulase-negative staphylococcus (12.0%), Streptococcus species (24.2%), Escherichia coli (7.7%), Pseudomonas aeruginosa (14.3%), bacilli species (11.0%). The study showed that there was a significant difference in the prevalence of bacilli species (p= 0.017) and E. coli (p= 0.015) among the study group. The results from total bacterial count indicated that toilet door handles had the highest bacterial load compared to office door handles and classrooms. Antibiotic susceptibility testing of isolates showed that all bacteria were resistant and intermediately resistant to commonly used antibiotics except for Escherichia coli that was susceptible to amoxicillin Conclusion and recommendations: The study reveals that door handles are a considerable source of pathogenic bacteria thus play a major role in the transmission of diseases caused by such bacteria. Further studies could be done and different study groups could be included for example routinely opened doors and the doors which are not routinely opened.